Nonsurgical Endodontic Retreatment of a Cystic Apical Lesion Associated with Root Resorption: A Promising Approach - Saeed Asgary (Case Reports in Clinical Practice)
This case report highlights the successful management of a cystic apical lesion associated with root resorption through nonsurgical endodontic retreatment, utilizing calcium-enriched mixture (CEM) cement as an obturating biomaterial. A 35-year-old woman presented with mild discomfort in the mandibular right first molar (#46), with radiographic evidence of a well-defined radiolucent lesion at the apex of the mesial root. The tooth had a history of previous failed endodontic treatment with poor root canal obturation, indicating internal root resorption. Nonsurgical endodontic retreatment was performed, and the canals were filled/sealed with CEM cement. Follow-up radiographs showed a gradual reduction in the size of the cystic lesion. At 54 months, complete bone healing of the cystic apical lesion was evident. This case report provides clinical evidence supporting the potential efficacy of nonsurgical endodontic retreatment using CEM cement in managing certain cystic apical lesions, offering a promising alternative to traditional surgical enucleation, even in cases with inflammatory root resorption. Further research is needed to validate the long-term efficacy of this approach in larger patient populations.